THE INFLUENCE OF MACHIAVELLIAN TO MODERATE TASK COMPLEXITY AND LOCUS OF CONTROL AS ANTESEDEN OFDYSFUNCTIONAL AUDIT BEHAVIOR - Riandanu, Andara Utami; Jalil, Fitri Yani (Prosiding International conference on Information Technology and Business (ICITB), 2018)
The purpose of this research is to analyze the influence of Machiavellian to moderate task complexity and locus of control as anteseden of dysfunctional audit behavior. This research was done in Public Accounting Firmof the DKI Jakarta Province. This research was using eighty sevent respondents as sample. Data were analyzed using moderate regression analyzed in SPSS. The result of this research showed that task complexity and locus of control partially effect to the dysfunctional audit behavior. Machiavellian can be a moderating for task complexity and dysfunctional audit behavior. But Machiavellian can’t be a moderating for locus of control and dysfunctional audit behavior. Keywords: Task Complexity; Locus of Control; Machiavellian;Dysfunctional Audit Behavior